Masticatory muscle tendon-aponeurosis hyperplasia: A new clinical entity of limited mouth opening - Tsuyoshi Sato, DDS, PhD; Tetsuya Yoda (Elsevier, 2016)
Limited mouth opening is a common health problem that interferes with eating, makes examination of the oral cavity difficult, and may increase the mortality rate during emergency intubation. Here we introduce a disease designated as masticatory muscle tendon-aponeurosis hyperplasia, which is a new clinical condition of limited mouth opening. Most oral surgeons and dentists are still unaware of this disease condition, thus increasing the risk of incorrect diagnosis as some other disease, such as temporomandibular joint disorder. We will review the clinical features, epidemiology, pathophysiology, etiology, diagnosis, treatment, and prognosis of this disease and also appraise the literature available on the subject.